Latent class analysis of bipolar disorder symptoms and suicidal ideation and behaviors. (8th July 2020) - Au, Josephine S.; Martinez de Andino, Ana; Mekawi, Yara; Silverstein, Madison W.; Lamis, Dorian A.
Abstract: Individuals with bipolar disorder are at increased risk of dying by suicide compared to healthy controls and those with unipolar depression. Previous studies show that depressive symptoms and mixed episodes of mania and depression are related to suicide. However, most of these studies adopt a variable‐centered approach to understanding how specific symptoms relate to suicidal ideation, without addressing how these symptoms and symptom profiles relate to suicidal behaviors. Objectives: Using latent class analysis, this study adopts a person‐centered approach to examine whether subtypes of patients with bipolar disorder differ in their levels of suicidal ideation and behaviors. Methods: A total of 150 patients from a behavioral health outpatient clinic were recruited. Latent classes were generated based on self reports of their depressive and manic symptoms. Results: Five classes of patients with bipolar disorder were identified, namely, a minimal symptom, mania, moderately depressed, severely depressed, and mixed depression‐mania subtypes. Those in the severely depressed and mixed depression‐mania groups reported significantly higher levels of suicidal ideation and behaviors compared to the other groups. Conclusions: Our findings provide further support for the strong relationship between depressive symptoms and suicidality. These findings are significant as they shed light on the different suicide risk profiles among a heterogenous group of patients with bipolar disorder. Name of clinical trial: Suicidal Behavior in Patients Diagnosed with Bipolar Disorder: The Roles of Biological and Childhood and Adult Environmental Risk Factors. ClinicalTrials.gov Identifier: NCT02604277.